The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.5195/ijms.2022.1288
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Perceptions, Knowledge, and Competence in Treating Neurodivergent, Disability, and Chronic Illness (NDCI) Populations: Results from a Cross-Sectional Study

Abstract: Background: Globally, Neurodivergent, Disability, and Chronic Illness (NDCI) populations face significant health disparities. Lack of physician knowledge about NDCI is a key mechanism underlying these disparities. The current study aimed to describe medical students’ perceptions, knowledge, and competence regarding NDCI. Methods: A cross-sectional study was carried out using an online survey of medical students at a large public university with no NDCI-specific curriculum (n = 97; response rate = 18%). The sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Therefore, the results of this study are not intended to judge or compare the achieved competence of participants. Instead, ratings of subjective competence are known to reflect students' confidence, attitude, and motivation 27–29 . The lack of confidence in students' self‐perceived competence to deal with a highly prevalent disorder thus raises serious concerns regarding the medical care for these patients and be a causative factor in the problems and shortcomings of medical care for IBS patients in Germany that have been documented on a large database 1,30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the results of this study are not intended to judge or compare the achieved competence of participants. Instead, ratings of subjective competence are known to reflect students' confidence, attitude, and motivation 27–29 . The lack of confidence in students' self‐perceived competence to deal with a highly prevalent disorder thus raises serious concerns regarding the medical care for these patients and be a causative factor in the problems and shortcomings of medical care for IBS patients in Germany that have been documented on a large database 1,30 …”
Section: Discussionmentioning
confidence: 99%
“…Instead, ratings of subjective competence are known to reflect students' confidence, attitude, and motivation. [27][28][29] The lack of confidence in students' self-perceived competence to deal with a highly prevalent disorder thus raises serious concerns regarding the medical care for these patients and be for IBS patients in Germany that have been documented on a large database. 1,30 Finally, the overall response rate of 13.3% achieved with this online survey is lower than rates that are seen with other surveys, especially when participants have known personal relations to the subject of the survey.…”
Section: Discussionmentioning
confidence: 99%
“…Adnan Mujanovic, 1 Vincent Kipkorir, 2 Cesare Mercalli, 3 Arkadeep Dhali, 4 Purva Shah, 5 Camila Velandia, 6 Ciara Egan, 7 Mihnea-Alexandru Găman, 8 Juan C. Puyana, 9 Francisco J. Bonilla-Escobar. 10 Medical education has had a dependence on the foundation of scientific evidence in order to ensure the provision of the best patient care.…”
Section: The Ijms World Conference Of Medical Student Research and An...mentioning
confidence: 99%
“…One of them is populations belong to the Globally, Neurodivergent, Disability, and Chronic Illness (NDCI) specter. 9 A group from the University of California performed a crosssectional study to check medical students' perceptions, knowledge, and competence regarding NDCI. 1 in 10 participants reported that their medical school included the NDCI population in their curriculum, but also that most of their knowledge on this cohort comes from their personal experience and media outlets and not from academical setting.…”
Section: Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation